2012
DOI: 10.1007/s00018-012-1171-6
|View full text |Cite
|
Sign up to set email alerts
|

Reelin-Disabled-1 signaling in neuronal migration: splicing takes the stage

Abstract: Reelin-Disabled-1 (Dab1) signaling has a well-established role in regulating neuronal migration during brain development. Binding of Reelin to its receptors induces Dab1 tyrosine phosphorylation. Tyrosine-phosphorylated Dab1 recruits a wide range of SH2 domain-containing proteins and activates multiple signaling cascades, resulting in cytoskeleton remodeling and precise neuronal positioning. In this review, we summarize recent progress in the Reelin-Dab1 signaling field. We focus on Dab1 alternative splicing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 83 publications
0
41
0
Order By: Relevance
“…Phosphorylated Dab1 acts as a signaling platform binding a variety of proteins involved in further down-stream signaling events (40). A central knot in this Reelin signaling network is the activation of PI3K (8), which leads to the phosphorylation of PKB/Akt (41) and activation of cofilin via LIMK1 (11).…”
Section: Resultsmentioning
confidence: 99%
“…Phosphorylated Dab1 acts as a signaling platform binding a variety of proteins involved in further down-stream signaling events (40). A central knot in this Reelin signaling network is the activation of PI3K (8), which leads to the phosphorylation of PKB/Akt (41) and activation of cofilin via LIMK1 (11).…”
Section: Resultsmentioning
confidence: 99%
“…2C, lane 1)) most likely results from a protein expressed by 3T3 fibroblasts incidentally cross-reacting with this antibody because earlier experiments using 3T3 cells clearly showed that Dab1 is not expressed by these cells (34). To verify this result, we performed the same Western blot analysis using an antibody specific for chicken Dab1-E (33), and, as demonstrated in Fig. 2C, lanes 4-6, this antibody only reacts with the Dab1-E-fusion protein.…”
Section: Figure 2 Expression Of Components Of the Reelin Signaling Pmentioning
confidence: 91%
“…The downstream primer specific for the E form is located in exon 9a, which is only present in the transcript for the E variant. The downstream primer specific for the L form is located in exon 8, which is absent from the E variant (33). Both primer pairs produced the specific product corresponding to transcripts for Dab1-E and Dab1-L (verified by sequencing) with mRNA from follicles at different stages of development and granulosa cells.…”
Section: Figure 2 Expression Of Components Of the Reelin Signaling Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Disturbed Reelin signaling has also been associated with neurological diseases such as Alzheimer disease, epilepsy, and schizophrenia (7)(8)(9)(10). Interaction of Reelin with VLDLRs at the cell surface induces signaling and tyrosine phosphorylation of the protein Dab1 (Disabled-1) via the Src family of kinases (11)(12)(13). Phosphorylated Dab1 then transmits the Reelin signal into the cell and influences the cytoskeleton and the expression of specific genes (9,13,14).…”
mentioning
confidence: 99%